Novel Agmatine Derivatives in Maerua edulis With Bioactivity Against Callosobruchus maculatus, a Cosmopolitan Storage Insect Pest - Stevenson, Philip C.; Green, Paul W. C.; Farrell, Iain W.; Brankin, Alice; Mvumi, Brighton M.; Belmain, Steven R. (Frontiers in Plant Science, 2018)
Food security in developing countries is threatened by crop pests and ectoparasites in livestock. Strategies for their management still rely on synthetic pesticides which are not always effective and the active ingredients persist in the environment with negative consequences for beneficial arthropods, farmers and consumers, hence necessitating research on sustainable alternatives. Botanical insecticides are increasingly relevant, typically having lower impacts on users, consumers and the environment. One example is the southern African shrub the Blue bush-berry, Maerua edulis. Recent work reported effective pest control using this plant species against cattle ticks, storage beetles and vegetable pests. However, little is known about the chemistry underlying activity and this is essential to optimize its use. Here, we identified two novel plant chemical structures, the E and Z isomers of cinnamoyl-4-aminobutylguanidine along with the E and Z isomers of 4-hydroxycinnamoyl-4-aminobutylguanidine in the leaves of M. edulis. We isolated these compounds from the leaves and elucidated their chemical structures using various spectroscopic techniques including High Resolution Mass Spectrometry and Nuclear Magnetic Resonance Spectroscopy. We also identified a further 11 closely related structures of which 6 are tentatively reported here for the first time. Stachydrine and 3-hydroxystachydrine were also identified in the leaf extract, and occurred at very high concentrations; up to 2% w/w of dry leaves. We tested these two compounds, along with the 4 main cinnamoylamides and the crude M. edulis leaf extract against the cowpea bruchid Callosobruchus maculatus at concentrations equivalent to those present in extracts used by smallholder farmers. Mortality of insects exposed to crude plant extracts after 72 h was significantly higher than the untreated control although still lower than for insects exposed to rotenone, the positive control. The two new compounds and stachydrine showed similar activity to the crude extracts suggesting that these compounds explained the activity of the extract. After 6 days, the mortality of insects exposed to crude extracts and isolated compounds was similar to that recorded with the positive control. The stachydrine fraction and the E and Z isomers of cinnamoyl-4-aminobutylguanidine also inhibited oviposition activity in fecund female beetles. Our data show that methanol extracts of M. edulis were toxic to C. maculatus and inhibited oviposition even at 0.1% w/v so these foliar chemicals may explain the activity of the plant material. We also synthesized the amides which facilitated structural elucidation, produced adequate quantities for testing and demonstrated the potential for commercial synthesis.